Beliefs about Climate Beliefs: The Importance of Second-Order Opinions for Climate Politics. Issue 4 (4th December 2017) - Mildenberger, Matto; Tingley, Dustin
Abstract : When political action entails individual costs but group-contingent benefits, political participation may depend on an individual's perceptions of others' beliefs; yet detailed empirical attention to these second-order beliefs – beliefs about the beliefs of others – remains rare. We offer the first comprehensive examination of the distribution and content of second-order climate beliefs in the United States and China, drawing from six new opinion surveys of mass publics, political elites and intellectual elites. We demonstrate that all classes of political actors have second-order beliefs characterized by egocentric bias and global underestimation of pro-climate positions. We then demonstrate experimentally that individual support for pro-climate policies increases after respondents update their second-order beliefs. We conclude that scholars should focus more closely on second-order beliefs as a key factor shaping climate policy inaction and that scholars can use the climate case to extend their understanding of second-order beliefs more broadly.